2018
DOI: 10.1016/j.ijid.2018.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus genotyping among women with cervical abnormalities in Ulaanbaatar, Mongolia

Abstract: Few studies on human papillomavirus (HPV) have been conducted in Mongolia. This study was performed to evaluate the prevalent HPV genotypes and their associations with cytology and demographic and behavioral characteristics in Mongolian women with cervical abnormalities. Methods: Exfoliated cell samples of 100 women who had a previous history of cervical abnormality were collected. Cytological interpretation was conducted microscopically and HPV genotyping was performed using the Roche Linear Array test. Study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 20 publications
1
21
0
Order By: Relevance
“…The prevalence of multiple HPV infections among normal samples ranges from 2.6–20.2% while such infections are reported to be higher in case of cervical abnormalities and lesions [15,18,24,34]. In a recent study conducted among 100 women with cervical abnormality, 68% of the samples demonstrated multiple HPV infections [35]. The HPV subtypes, therefore, may exhibit both cooperative and competitive interactions during cervical carcinogenesis [36] which needs to be validated using molecular studies.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of multiple HPV infections among normal samples ranges from 2.6–20.2% while such infections are reported to be higher in case of cervical abnormalities and lesions [15,18,24,34]. In a recent study conducted among 100 women with cervical abnormality, 68% of the samples demonstrated multiple HPV infections [35]. The HPV subtypes, therefore, may exhibit both cooperative and competitive interactions during cervical carcinogenesis [36] which needs to be validated using molecular studies.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that the prevalence of HPV infection in women with abnormal cervical cytology was 47.0% to 72.8% [15,16]. HPV prevalence increased with increasing severity of cervical lesions from 12% in normal cytology to 89% in invasive cervical cancer [17].…”
Section: Introductionmentioning
confidence: 99%
“…To date, more than 100 HPV genotypes have been identified [5], of which approximately 40 HPV types are associated with the genital tract infection [6]. Among the numerous members of the HPV family, 15 HR-HPV genotypes (types 16,18,31,33,35,39,45,51,52,53,56,58,59, 66 and 68) are etiologically associated with more than 98% of cervical cancers. Effective prophylactic vaccines against the most important carcinogenic HPV types are available, but they do not cover main types of HPV in different countries and regions [7].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of HPV infection in women with abnormal cervical cytology is 47.0%-72.8%. 18,19 HPV prevalence increases with increasing severity of cervical lesions: from 12% in normal cytology to 89% in invasive cervical cancer. 20 The prevalence of HR-HPV in women with abnormal cervical cytology is 92.4%, significantly higher than those with normal cytology (71%).…”
Section: Introductionmentioning
confidence: 99%